Optimizing the Role of Higher Education in Increasing the Response Rate of the Online Population Census 2020 in Semarang: Optimalisasi Peran Perguruan Tinggi dalam Meningkatkan Respon Rate Sensus Penduduk Online 2020 di Semarang - Nur, Indah Manfaati; Al Haris, M.; S.A.P., Rangga Sa'adillah; Hasyim, Mochamad (Jurnal Soeropati, 2023)
The online population census was first launched in 2020. The purpose of the online population census 2020 is to provide data on the number, composition, distribution, and characteristics of the Indonesian population towards one Indonesian population data and provide demographic parameters and population projections and other population characteristics for population projections and SDGs indicators. These data are needed by the government as one of the bases for making decisions or policies in order to be able to accommodate all existing interests. This innovation with an online census approach is undoubtedly inseparable from social problems or constraints. Social, economic, and geographic factors affect the literacy of information and communication technology in society. The factual conditions in the field encouraged the team community service to take a strategic role by carrying out community service activities in Kecamaran Pabelan, Semarang Regency, in the form of online population census 2020 assistance activities. Mentoring methods are carried out by providing counseling, socialization, and technical guidance to the Public. The results achieved from this assistance to partners were an increase in the community response rate in Semarang Regency, more partners could participate and it was easier to fill data in the online population census 2020.